An Unusual Case of Paraquat-Induced Rhabdomyolysis and Hepatic Injury Presenting With Takotsubo Cardiomyopathy - Sara Jaka MD; Theingi Tiffany Win MD; Fowrooz Joolhar MD; Arash Heidari MD; Leila Moosavi MD (SAGE Publishing, 2021)
Takotsubo cardiomyopathy (TCM) is a syndrome of reversible left ventricular systolic dysfunction that, at presentation, can be easily conflated with acute coronary syndrome. TCM has a clinical preponderance for older, postmenopausal females. We report on a patient's case who presented with complaints of upper and lower extremity weakness with evidence of rhabdomyolysis and hepatic injury. Her occupation as a field worker exposed her to a toxic chemical known as paraquat, which has been banned by multiple countries across the world; a chemical we presume culminated in both. The subsequent clinical cascade and resulting acute physiological illness and emotional distress primed her to develop TCM. However, she neither endorsed chest pain nor dyspnea. Her subtle clinical presentation could have led to a missed diagnosis as she was also not in a fluid overloaded state consistent with the depressed left ventricular function discovered on transthoracic echo. The diagnostic uncertainty until coronary angiography is obtained, and its association with severe and acute emotional and physical stress prompts to a greater reliance on patient history to identify occupational and toxic exposures that can contribute to its development.